2011
DOI: 10.1002/emmm.201100136
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulation of BRCA1 expression by miR‐146a and miR‐146b‐5p in triple negative sporadic breast cancers

Abstract: Germ-line mutations in the BRCA1 gene strongly predispose women to breast cancer (lifetime risk up to 80%). Furthermore, the BRCA1 protein is absent or present at very low levels in about one third of sporadic breast cancers. However, the mechanisms underlying BRCA1 somatic inactivation appear multiple and are still not fully understood. We report here the involvement of miR-146a and miR-146b-5p that bind to the same site in the 3′UTR of BRCA1 and down-regulate its expression as demonstrated using reporter ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
181
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 240 publications
(194 citation statements)
references
References 61 publications
13
181
0
Order By: Relevance
“…17,18 Here, we chose to screen in familial breast cancer cases from the GENESIS study, the coding region of two miR genes, MIR146A and MIR146B, producing miR-146a and miR-146b-5p, respectively, as it has been shown that they regulate the expression of BRCA1. 12,13,19 A common MIR146A variant, rs2910164, which resides in the region encoding the sequence complementary to the mature miR in the stem-loop structure of the pre-miR, is one of the most extensively studied miR-related genetic variant. In the most recent meta-analysis published to date, no evidence of association between rs2910164 and breast cancer risk was obtained, although association was observed with bladder, cervical, liver and lung cancers, as well as with oral squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Here, we chose to screen in familial breast cancer cases from the GENESIS study, the coding region of two miR genes, MIR146A and MIR146B, producing miR-146a and miR-146b-5p, respectively, as it has been shown that they regulate the expression of BRCA1. 12,13,19 A common MIR146A variant, rs2910164, which resides in the region encoding the sequence complementary to the mature miR in the stem-loop structure of the pre-miR, is one of the most extensively studied miR-related genetic variant. In the most recent meta-analysis published to date, no evidence of association between rs2910164 and breast cancer risk was obtained, although association was observed with bladder, cervical, liver and lung cancers, as well as with oral squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Garcia et al reported that the highest levels of miR-146a and miR-146b-5p were found in BL in vitro and TNBC patients. 96 On the other hand, the BRCA1/2 gene is a well-characterized cancer susceptibility gene that is associated with hereditary breast and ovarian cancer. 97,98 Shen et al 99 suggested that genetic polymorphisms in the miR-146a gene might be associated with young age in familial cases of breast or ovarian cancer.…”
Section: Mirna In Triple-negative Breast Cancermentioning
confidence: 99%
“…Although the ovarian cancer genome atlas reported a low incidence of mutations in other genes involved in the Fanconi complex, 256 there may be other mechanisms involved, including miRNA-mediated downregulation of BRCA1, 257 which has been reported in triple-negative breast cancers. 258 Anecdotically, a remarkable response to mitomycin was observed in a patient with pancreatic cancer harbouring biallelic PALB2 mutations. 259 Although PARP inhibitors administered as monotherapy was found ineffective in triple-negative breast cancer, experimental evidence has indicated synergistic lethality between cisplatin and PARP inhibitors in triple-negative breast cancer cells not harbouring BRCA1/2 mutations.…”
Section: Homologous Recombination Repairmentioning
confidence: 99%